THE IMPORTANCE OF RECYCLING SOLID WASTE IN ORGANIZATIONS - BRAGA JUNIOR, Sergio Silva; PINHEIRO, Luciane Ribeiro Dias (Revista Brasileira de Engenharia de Biossistemas, 2013)
In order to understand the purpose of recycling, one must understand the meaning of trash, not in the sense of dirt, but as something useful, and may be an alternative for reuse, generating sustainability within its overall context of social responsibility (Portilho, 2010). Be that as an alternative to development, this concern of organizations has become something essential for survival in the market, an extremely important initiative, becoming the mirror of a society increasingly demanding and concerned about the world. It is important to note that through the practice of recycling of solid waste, which is the primary focus analyzed are associated those benefits, such as income generation, and ecological awareness, reducing the impact on the environment. Thus, this work aims to generate an overview of sustainability with a focus on solid waste recycling through initiatives of organizations listed on BM & FBOVESPA, checking that their actions represent attitudes that generate high-impact and benefits in various aspects. As a result it was observed that the main impact being generated through environmental awareness worldwide, reflecting a generation with attitudes driven by new vision of concern for the future of other generations.